Occupational hypersensitivity pneumonitis: an EAACI position paper. Issue 6 (11th March 2016) - Quirce, S.; Vandenplas, O.; Campo, P.; Cruz, M. J.; de Blay, F.; Koschel, D.; Moscato, G.; Pala, G.; Raulf, M.; Sastre, J.; Siracusa, A.; Tarlo, S. M.; et al.
Abstract: The aim of this document was to provide a critical review of the current knowledge on hypersensitivity pneumonitis caused by the occupational environment and to propose practical guidance for the diagnosis and management of this condition. Occupational hypersensitivity pneumonitis (OHP) is an immunologic lung disease resulting from lymphocytic and frequently granulomatous inflammation of the peripheral airways, alveoli, and surrounding interstitial tissue which develops as the result of a non‐IgE‐mediated allergic reaction to a variety of organic materials or low molecular weight agents that are present in the workplace. The offending agents can be classified into six broad categories that include bacteria, fungi, animal proteins, plant proteins, low molecular weight chemicals, and metals. The diagnosis of OHP requires a multidisciplinary approach and relies on a combination of diagnostic tests to ascertain the work relatedness of the disease. Both the clinical and the occupational history are keys to the diagnosis and often will lead to the initial suspicion. Diagnostic criteria adapted to OHP are proposed. The cornerstone of treatment is early removal from exposure to the eliciting antigen, although the disease may show an adverse outcome even after avoidance of exposure to the causal agent.